Parameter Selection of Dynamic Reactive Power Compensator (DRPC) - Arunprasanth, S.; Bandara, R.W.K.M.R.K.D.; Tharaka, R.M.R.; Atputharajah, A.; Fernando, M.A.R.M.; Abeyrathna, S.G.; Navarathne, D.N.; Tennakoon, A.P.; Alagoda, S. (University of Jaffna, 2000)
This poster presents the complete simulation study of a Dynamic Reactive Power Compensator (DRPC), which is one of the Flexible Alternative Current Transmission System (FACTS) devices. Continuous and smooth reactive power compensation will improve the power system performance. This brings down voltage fluctuation, power loss in the transmission system and threat on instability while reducing the kVA demand. Further the transmission lines can be utilized to transmit more active power while improving the reliability of the supply. A control system for DRPC has been developed; simulated using EMTDC/PSCAD program and results are provided.